"The best laid plans…" Evaluation of a pubertally adjusted 0.4th centile in new UK school age charts. (24th May 2012) - Moon, JS; Rudolf, M; Gibson, P; Butler, G; Wright, CM
Abstract : Background and aims: Assessing growth around puberty is difficult and children with later onset of puberty may be mislabelled as abnormal. When designing new school age charts a lower pubertally adjusted (PA) 0.4th centile was added to the prototype chart for children aged 8-13 still in pre-puberty, with shading between this and the standard 0.4th centile. We aimed to evaluate users' understanding of this feature and its impact on clinical judgement. Methods: Three workshops were performed with GP trainees (N=26) and paediatricians (N=48). After explanatory slides about the new charts, participants completed workbooks which tested aspects of the new charts using plotting and interpretation. These included two standardised scenarios where a height at 11 years was in the shaded area between the conventional and the PA 0.4th centile. One was a pre-pubertal girl growing steadily within the PA normal range and the other a girl in-puberty with declining growth, dropping below the PA 0.4th centile. These were permutated through two questionnaires, with each respondent viewing only one. Results: The pubertal phase was reported correctly by 93% of the 74 respondents. Only 61% (23) viewing the pre-pubertal child recognised that she was above the PA 0.4th centile, though 79% (30) recognised she required no further investigation. Of those viewing the pubertal child 31% (11) incorrectly stated that she was above the PA 0.4th centile and only 47% (17) recognised she required further investigation. In 2/3 sessions more specific questions were asked about centile position and 88% (42/48) correctly reported the unadjusted centile position (<0.4th). Of these, only 10/18 then recognised that the pre-pubertal child was above PA 0.4th centile while 5/20 incorrectly stated that the in-puberty child was on or above the PA 0.4th centile. Unfavourable comments, describing the pubertal element as complex and confusing were made by 49% respondents. Conclusions: The proposed shaded area was ineffective at identifying lower risk children and seemed to create false reassurance concerning children with disordered growth in puberty, so the design has now been radically modified. This study shows that formal evaluation of 'improvements' to growth charts is essential.